2011
DOI: 10.1002/wcms.30
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory with London dispersion corrections

Abstract: Dispersion corrections to standard Kohn-Sham density functional theory (DFT) are reviewed. The focus is on computationally efficient methods for large systems that do not depend on virtual orbitals or rely on separated fragments. The recommended approaches (van der Waals density functional and DFT-D) are asymptotically correct and can be used in combination with standard or slightly modified (short-range) exchange-correlation functionals. The importance of the dispersion energy in intramolecular cases (conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
1,943
0
25

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,286 publications
(1,990 citation statements)
references
References 120 publications
22
1,943
0
25
Order By: Relevance
“…The basis set superposition error [5] was not corrected in the clusters since previous studies have shown that the basis set superposition error has little impact on the rotational barriers [2] while the computational cost is significant. All the calculations in the clusters were performed at the B3LYP/6-31G(d) level with the Grimme's D3BJ empirical correction for the London dispersion [19,20].…”
Section: Electronic Structure Calculationsmentioning
confidence: 99%
“…The basis set superposition error [5] was not corrected in the clusters since previous studies have shown that the basis set superposition error has little impact on the rotational barriers [2] while the computational cost is significant. All the calculations in the clusters were performed at the B3LYP/6-31G(d) level with the Grimme's D3BJ empirical correction for the London dispersion [19,20].…”
Section: Electronic Structure Calculationsmentioning
confidence: 99%
“…Nonetheless, besides more complex formalisms as adiabatic-connection fluctuation-dissipation theorem [81] or the random-phase approximation [82], practical schemes introduce semi-classically (at no extra cost) the missing dispersion energy (E DX ) into the computational treatment by means of a function like [83][84][85]:…”
Section: Extensions 231 Non-covalent Interactionsmentioning
confidence: 99%
“…[6][7][8] Over the last years, much effort within the DFT framework has been made to develop approximations that allow the accurate treatment of dispersion forces between molecular entities. [9][10] Among the most modern approaches, the atom-pairwise dispersion-corrected DFT approach, developed by Grimme et al, known in its current version as DFT-D3, is a manner of dealing with NCIs with a reasonable compromise between computational cost and accuracy. [11][12][13][14] A less popular but seamless and general approach known as van der Waals Density Functional Theory (vdW-DFT) has recently received a great deal of attention due to its low degree of empiricism.…”
Section: Introductionmentioning
confidence: 99%